Treatment of nursing bottle caries with ribbond - Ritu Jindal; Gurlal Singh Brar (Wolters Kluwer Medknow Publications, 2013)
Ribbond is a biocompatible, esthetic material made from high-strength polyethylene fiber. Lenowoven polyethylene ribbon (Ribbond) has been used successfully for tooth splinting, replacement of missing teeth, reinforcement of provisional acrylic resin fixed partial dentures, and orthodontic retention. This article presents the application of this polyethylene ribbon - RIBBOND - for the treatment of nursing bottle caries. To conclude we suggest that this combined technique of polyethylene fibers and composite material could be a very efficient alternative procedure to conventional treatment plans in pedodontic practice, with excellent esthetics and functional results.